MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SATUAN BERAT MELALUI MEDIA PUZZLE KOTAK BAGI ANAK TUNARUNGU DIKELAS IV SLB CENTER KOTA PAYAKUMBUH - Maizar - (Universitas Negeri Padang, 2016)
ABSTRACTThis research is motivated by problem that appear in the field, three children with the deaf on grade D IV/B in SLB N Center Payakumbuh who have the problem to understanding the weight concept on Mathematic lesson. It has seen children capability to understanding weight concept like S, F, and DN and can’t to answer it on the test. Under these conditions, this study aims to demonstrate the use of the puzzle box media. The methodology of this research is Classroom Action Research by collaborated with friend to be an observer. Results of this study indicate that the media puzzle box can be raised the understanding of children with deaf problem to know the weight concept, like S, F, DN. Keyword : deaf children, weight concept, puzzle box media